Renin–angiotensin–system inhibitors and the risk of exacerbations in chronic obstructive pulmonary disease: a nationwide registry study. Issue 1 (7th March 2023) - Vilstrup, Frida; Heerfordt, Christian Kjer; Kamstrup, Peter; Hedsund, Caroline; Biering-Sørensen, Tor; Sørensen, Rikke; Kolekar, Shailesh; Hilberg, Ole; Pedersen, Lars; Lund, Thomas Kromann; Klausen, Tobias Wirenfeldt; Skaarup, Kristoffer Grundtvig; et al.
Abstract : Objective: The renin–angiotensin system (RAS) has been shown to play a role in the pathogenesis of chronic obstructive pulmonary disease (COPD) because of the inflammatory properties of the system. Many patients with COPD use RAS-inhibiting (RASi) treatment. The aim was to determine the association between treatment with RASi and the risk of acute exacerbations and mortality in patients with severe COPD. Methods: Active comparator analysis by propensity-score matching. Data were collected in Danish national registries, containing complete information on health data, prescriptions, hospital admissions and outpatient clinic visits. Patients with COPD (n=38 862) were matched by propensity score on known predictors of the outcome. One group was exposed to RASi treatment (cases) and the other was exposed to bendroflumethiazide as an active comparator in the primary analysis. Results: The use of RASi was associated with a reduced risk of exacerbations or death in the active comparator analysis at 12 months follow-up (HR 0.86, 95% CI 0.78 to 0.95). Similar results were evident in a sensitivity analysis of the propensity-score-matched population (HR 0.89, 95% CI 0.83 to 0.94) and in an adjusted Cox proportional hazards model (HR 0.93, 95% CI 0.89 to 0.98). Conclusion: In the current study, we found that the use of RASi treatment was associated with a consistently lower risk of acute exacerbations and death in patients with COPD. Explanations to these findings include real effect, uncontrolled biases, and—less likely—chance findings.